An Empirical Study of Learning Object Acceptance in Multimedia Learning Environment - Lau, Siong Hoe; Woods, Peter Charles (IBIMA Publishing, 2008)
The purpose of this study was to develop Learning Object Acceptance Model (LOAM) to examine the underlying factors and causal relationships that determine learners' behavioral intention to use multimedia learning objects in higher education. This study called for the 342 respondents to progress through two phases of learning objects participation: Introduction and Direct-use experience. Structural Equation Modeling (SEM) was used to evaluate data from the resultant surveys with the AMOS 4.0. The results showed that the study model produced measurement and structural models with adequate model fits. Learners' perceived of usefulness and ease of use a fully mediated the relationship between learning object characteristics and behavioral intention. However, individual characteristics were found to have no statistically significance on behavioral intention in this context.